Release bioactive peptides from enzymatic hydrolysated soybean by Alcalase and Protamex using response surface methodology - Quynh Hoa, Nguyen Thi; Thi Anh Dao, Dong (Vietnam Journal of Science and Technology, 2017)
Bioactive peptides have been defined as specific protein fragments that have a positive impact on body functions and conditions and may ultimately influence health. The objective of this paper is to study the enzymatic hydrolysis process of soy protein to produce bioactive peptides. To study the action of Alcalase and Protamex on the proteins of soybean, the influence of the temperature, pH, substrate concentration, enzyme concentration and hydrolysis time on the soluble protein recovery of the soy proteins was evaluated. The soyprotein was hydrolyzed by two different enzymes. Response surface methodology was applied to optimize the hydrolysis capicity. The dried hydrolysate was low to medium molecular weight bioactive peptides. The results of amino acid analysis showed that the composition of amino acid of soy protein and its hydrolysate obtained under the optimized condition was considerably enriched in essential amino acids and ensure the nutrition and safety for human consumption